Knee and ankle muscles coactivations in breaststroke swimming kick and recovery: Exploratory approach - Guignard, B.; Olstad, B. H.; Simbaña Escobar, D.; Lauer, J.; Kjendlie, P.-L.; Rouard, A. H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The specificities of body position in breaststroke induce important lower limbs solicitations for the swimmers to propel themselves efficiently. Coactivations around the knee and ankle might appear during the powerful leg extension (i.e. push) and for leg replacement (i.e. recovery). The purpose of this exploratory study is to determine muscle activations and coactivations during these two phases at three different velocities. The EMG of four muscles was recorded (BF, RF, GAS and TA). The results showed important activations of the four muscles in the push, contrary to the recovery. However, no significant differences were found for the coactivations in the two phases and for the three velocities. These findings denoted the important resistances occasioned by aquatic environment, both in push and recovery phases, necessitating muscle coactivations to stabilise joints.